Bitumen-silica interactions in the presence of hydrophilic ionic liquids. (1st December 2018) - Sui, Hong; Ma, Guoqiang; Yuan, Yipu; Li, Qifeng; He, Lin; Wang, Yang; Li, Xingang
Highlights: The bitumen-silica interaction is highly dependent on the state of ionic liquids. Pure ionic liquid exerts strong resistance between the bitumen and silica. Ionic liquid in solution acts likes a surfactant in facilitating the oil-solid separation. A Helmholtz-like layer is formed by the [Emim] + on silica and bitumen surfaces. The positively charged Helmholtz-like layers allow the adhesion reduction between bitumen and silica. Abstract: Ionic liquids have been considered for application in petroleum separation (especially in unconventional oil production) as interfacial functional materials at pure state or aqueous solution state. Herein, the interactions between bitumen and silica in ionic liquids (i.e., [Emim][BF4 ]) aqueous solution and pure ionic liquids have been investigated by dynamic contact angle, atomic force microscopy (AFM) and sum-frequency generation spectroscopy (SFG). Results show that the addition of ionic liquids in water enhances the equilibrium degree of bitumen recession from silica surface, while negligible change has been observed when the bitumen coated plate was put into the pure ionic liquids. The force measurements by AFM demonstrate that the bitumen-silica adhesion force in different systems are in the order of: DI water >1 mM [Emim][BF4 ] > pure [Emim][BF4 ]. Results of SFG detection show that the addition of [Emim][BF4 ] in the aqueous solution strengthens the orientation of water molecules on the silica surface, while making the water molecules more disordered on the bitumen surface. Consequently, a positively charged Helmholtz-like layer is formed by the [Emim] + cations on negatively charged silica and bitumen surfaces.